LiteGreen: Saving Energy in Networked Desktops Using Virtualization - Das, Tathagata; Padala, Pradeep; Padmanabhan, Venkat; Ramjee, Ramachandran; Shin, Kang G. (USENIX Annual Technical Conference [BEST PAPER], 2010)
To reduce energy wastage by idle desktop computers in enterprise environments, the typical approach is to put a computer to sleep during long idle periods (e.g., overnight), with a proxy employed to reduce user disruption by maintaining the computer’s network presence at some minimal level. However, the Achilles’ heel of the proxy-based approach is the inherent trade-off between the functionality of maintaining network presence and the complexity of application-specific customization. We present LiteGreen, a system to save desktop energy by virtualizing the user’s desktop computing environment as a virtual machine (VM) and then migrating it between the user’s physical desktop machine and a VM server, depending on whether the desktop computing environment is being actively used or is idle. Thus, the user’s desktop environment is “always on”, maintaining its network presence fully even when the user’s physical desktop machine is switched off and thereby saving energy. This seamless operation allows LiteGreen to save energy during short idle periods as well (e.g., coffee breaks), which is shown to be significant according to our analysis of over 65,000 hours of data gathered from 120 desktop machines. We have prototyped LiteGreen on the Microsoft Hyper-V hypervisor. Our findings from a small-scale deployment comprising over 3200 user-hours of the system as well as from laboratory experiments and simulation analysis are very promising, with energy savings of 72-74%with LiteGreen compared to 32% with existing Windows and manual power management.
Best Paper